The Impact of Supply Activities on Building the Positioning of Enterprises in the International Market: "Hasnaoui" Group of Companies in Sidi-Bel-Abbas as a Case Study - Choukri, Kazi Aoual Mohammed; Mohamed, Zeradna (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aims to determine the importance of supply activities in building the enterprise’s positioning in the international market. In its theoretical framework, the study adopted the issue of international supply as an independent variable in addition to the strategy of positioning in the international market as a dependent variable. Hover, the practical framework of the study included identifying the impact of commitment to implement supply activities on the enterprise’s positioning in the international market. The supply activities consisted of procurement, transportation, storage, distribution, and packaging. The Hasnawi Group of Companies was chosen as an international enterprise to conduct the study. As for the study sample consisting of 42 individuals, it was randomly chosen. By analyzing the questionnaire using the Statistical Package for Social Sciences (SPSS V. 20), the results showed that the enterprise under study pays attention to international supply activities as a key factor in building international positioning. The study also found that there is a correlation and influence between the supply activities and the dimensions of positioning in the international market represented in quality, cost, delivery speed and brand. Notably, the storage and packaging activities had the greatest impact, which means that the company seeks to build its positioning internationally by providing products near the consumer, in addition to adopting a packaging policy that is consistent with the characteristics of the international marketing environment.
Keywords: International Supply; Positioning; International Markets